Commentaries on Foreign Assistance - Mensah, Moïse C.; Lattre, Anne de; Johnston, Bruce F. (International Food Policy Research Institute, 1987)
Ideally, an assessment of donor's impact on food strategies would require knowledge of "with aid" and "without aid" situations. This is not possible, as foreign aid has been and will remain for a long time a permanent feature of the development process in Africa. One way of assessing impact could be to establish that one dollar of foreign aid mobilizes or supports x dollars of domestic resources to produce y dollars' worth, or z tons, of food. However, it would need a better knowledge than is presently available of the amounts of external aid that go to food and to agriculture in general. While the disaggregation would be difficult, at least a reasonable approximation is necessary. Likewise, we need a better picture of the domestic resources made available by government, local communities, individual farmers, and so forth. Although we know that external aid is important, we do not know, apart from emergency food aid, how essential it is. Yet we must know this to adequately discuss donors' influence on national food strategies.